A comparison of the pre-socialist and socialist reception of Mark Twain in Slovenia - Trupej, Janko (Annales. Series historia et sociologia, 2021)
The present article analyses the reception of Mark Twain and his works in serial publications on the territory that now constitutes the Republic of Slovenia over a period of circa one hundred years, i.e. it compares Twain’s status in the pre-socialist era (until 1945) and the socialist era (1945–1991). The article addresses the extent to which the reception was affected by ideology and the contemporary political situation, as well as by the relations between the United States and the country of which the Slovenian territory formed part during a particular period of time.
Keywords: American literature; ameriška književnost; ideologija; ideology; literary translation; reception; socializem; Twain, Mark